2021
DOI: 10.3390/su13179989
|View full text |Cite
|
Sign up to set email alerts
|

Do Tourism and Institutional Quality Asymmetrically Effects on FDI Sustainability in BIMSTEC Countries: An Application of ARDL, CS-ARDL, NARDL, and Asymmetric Causality Test

Abstract: The motivation of the study is to investigate the nature of the relationship between institutional quality, tourism, and FDI in BIMSTEC nations for the period 1996Q1–2018Q4. Exploring their nature of association, the study performed several panel econometric models, namely Panel ARDL, Nonlinear ARDL, and Toda-Yamamoto causality test, with symmetric and asymmetric effects of institutional quality and tourism. The results of the Wald test confirmed the long-run asymmetric relationship between institutional quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 135 publications
2
34
0
Order By: Relevance
“…As a result, efficiency is boosted by redistributing buying power from low-return customers to high-return ones. Additionally, finance is anticipated to combat poverty by boosting income and, in the long term, through improving health and education (Yang et al, 2021 ). This is because investment in skill development and services and physical infrastructure that promote health and lifespan is critical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, efficiency is boosted by redistributing buying power from low-return customers to high-return ones. Additionally, finance is anticipated to combat poverty by boosting income and, in the long term, through improving health and education (Yang et al, 2021 ). This is because investment in skill development and services and physical infrastructure that promote health and lifespan is critical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, urbanization has augmented the economy's financial development and promoted industrial development in remote areas, eventually leading to energy consumption and inefficient technological integration, resulting in environmental degradation [92]. Apart from energy demand escalation, urbanization has induced demand for infrastructural development, wastage management, and trade internationalization, eventually augmenting environmental degradation [93].…”
Section: Long-run and Short-run Symmetric Investigationmentioning
confidence: 99%
“…Note, nonetheless, that panel ARDL undertakes errors are cross-sectionally independent. Nevertheless, such perceived notions might produce spurious estimations in some situations and lead to badly predisposed estimates if the regressors' unobserved common factors are correlated (57)(58)(59). Chudik and Pesaran (60) Propose implementing Common Correlated Effects (CCE) approach in the context of panel ARDL models.…”
Section: Cs-ardlmentioning
confidence: 99%
“…Other scholars, likeZhang et al (2017),Töbelmann and Wendler (55), Zhao and Qamruzzaman(75)and Iqbal, Abbasi(76) have found that environmental innovations are beneficial to environmental prosperity. In contrast to Khan, Weili (1) and Yang, Qamruzzaman(58). According to Hodson, Brown(77), environmental innovation promotes successful energy integration by reducing energy costs and transition and improving environmental quality by cutting carbon emissions.…”
mentioning
confidence: 99%